ADVANTAGES AND DISADVANTAGES OF CLOUD COMPUTING - Plotņikovs, Aldis; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The paper defines cloud computing and describes the main cloud computing models, like software as a service (SaaS), platform as a service (PaaS) and infrastructure as a service (IaaS), than main advantages and disadvantages with concrete examples are given. The three advantages outlined in the paper are cost optimization, rapid access to computer resources and information sharing possibilities. The three disadvantages outlined are security, technology restrictions and unexpected service downtime.